SHIRPA as a Neurological Screening Battery in Mice. Issue 5 (17th May 2021) - Lalonde, Robert; Filali, Mohammed; Strazielle, Catherine
Abstract: The SmithKline, Harwell, Imperial College, Royal Hospital, Phenotype Assessment (SHIRPA) is a rapid battery of tests comprising 42 measurements of motor activity, coordination, postural control, muscle tone, autonomic functions, and emotional reactivity, as well as reflexes dependent on visual, auditory, and tactile modalities. Individual scores in SHIRPA are sensitive in detecting phenotypes of several experimental models of neural disease, especially cerebellar degeneration and Alzheimer disease, and combined subscores have been useful in estimating the impact of vascular anomalies and exposure to infectious agents. In cerebellar degeneration, weak forelimb grip, impaired wire maneuver and air righting, and negative geotaxis appear as prevalent features. Most of the measures in the battery are susceptible to change after gene modifications or physiological alterations. SHIRPA can be used both in adult mice and mice in the preweaning period to screen for sensorimotor function and emotional reactivity, not selective attention or memory. © 2021 Wiley Periodicals LLC Basic Protocol : Step‐by‐step procedure for SHIRPA